Ответ:
Пошаговое объяснение:
1. 6,4*(-5,8)=-37,12
-14,95/1,3=-11,5
2. 1,7(а-3)-5а= 1,7а-5,1-5а=3,3а-5,1=3,3·5-5,1=11,4
3. 3(4х-7,6)=0
12х-22,8=0
12х=22,8
х=22,8/12
х=1,9
4.((5 1/3-8)/1 7/9)/((2 5/9-3 2/3)·0,45)=(-8/3/16/9)/(-10/9·45/100)=-3/2/(-5/10)=3
5. 0,68·(-2,8)·4,8/1,7·0,32·4,8=-3,5
6. (2а-b)-(2a+b)= 2a-b-2a-b=-2b
3(b-c)+2(c-a)+(a+b)= 3b-3c+2c-2a+a+b=4b-c-a
7. 4(х-3)-16=5(х-5)
4х-12-16=5х-25
4х-5х=12+16-25
-х=3
х=-3
8. -4+(-2,3)+5,7+(-35)= -4-2,3+5,7-35=-33,6
9. 3,2-2,4(5с+2)= 3,2-12с-4,8=3,2-12·1/6-4,8=3,2-2-4,8=-3,6
10. 2(y-3)-7(y+1,5)=3,5
2y-6-7y-10,5=3,5
-5y=3,5+6+10,5
-5y=20
y=20/(-5)
y=-4